1999
DOI: 10.1159/000023458
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Noncomplexed ‘Big’ (10–18 kD) Forms of Insulin-Like Growth Factor-II by 12 Soft Tissue Sarcoma Cell Lines

Abstract: The paraneoplastic production of pro-insulin-like growth factor-II (IGF-II) forms causes tumour hypoglycaemias and presumably also has an effect on tumour cell growth. We investigated the molecular weights of IGF-II forms and their ability to form complexes with IGF binding proteins (IGFBPs) in conditioned culture media (CM) from 12 paediatric soft tissue sarcoma (STS) cell lines and from two healthy fibroblast lines. Untreated CM were separated by size exclusion chromatography using biocompatible HPLC. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…The findings presented here have also confirmed that IGFBP-2, IGFBP-3, and IGFBP-5 bind all IGF-II isoforms similarly to mature IGF-II, in agreement with Bond et al (16) but not with Elmlinger et al (17), who reported that pooled isolates of IGF-II isoforms from Ewing's sarcoma cell conditioned media appeared to retard binary complex formation with IGFBP-2 and IGFBP-3. Our approach has also confirmed early findings that IGFBP-3-based ternary complex formation by glycosylated IGF-II isoforms is severely compromised (16) and has refined these findings to show that big-IGF-II 1-87 and big-IGF-II 1-104 are the most potent at preventing its assembly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings presented here have also confirmed that IGFBP-2, IGFBP-3, and IGFBP-5 bind all IGF-II isoforms similarly to mature IGF-II, in agreement with Bond et al (16) but not with Elmlinger et al (17), who reported that pooled isolates of IGF-II isoforms from Ewing's sarcoma cell conditioned media appeared to retard binary complex formation with IGFBP-2 and IGFBP-3. Our approach has also confirmed early findings that IGFBP-3-based ternary complex formation by glycosylated IGF-II isoforms is severely compromised (16) and has refined these findings to show that big-IGF-II 1-87 and big-IGF-II 1-104 are the most potent at preventing its assembly.…”
Section: Discussionsupporting
confidence: 92%
“…However, results showing that pooled IGF-II isoforms from NICTH serum or tumor tissue form binary complexes with IGFBP-1 to -6 (16) contrast with studies demonstrating pooled IGF-II isoforms from conditioned Ewing's sarcoma media not forming binary complexes with IGFBP-2 and IGFBP-3 (17). Similarly, evidence shows that glycosylated IGF-II isoforms from NICTH tumor tissue can escape ternary complex with IGFBP-3 and ALS by retarding ALS recruitment (16), but it is unknown what contribution the individual IGF-II isoforms make in this respect and what effect this has on bioavailability.…”
Section: Insulin-like Growth Factor II (Igf-ii)mentioning
confidence: 98%
“…This elevated expression of IGFBP-2 might be promoted by autocrine/paracrine stimulation via IGF-II-and/or pro-IGF-forms, which tumors often secrete in large quantities (Yang et al 1996, Duguay et al 1998, Elmlinger et al 1999, Elmlinger et al 2001b. Thus, it is assumed that elevation of the IGFBP-2 production is part of a mechanism to compensate for the mitogenic and antiapoptotic effects of tumor-derived IGFs.…”
Section: Introductionmentioning
confidence: 99%
“…They are 11-17 kDa in size, contain 87 or 104 amino acids, respectively, and differ in glycosylation (10)(11)(12)(13)(14). It has been suggested that big IGF-II is biologically active but may have different activity in tumor cells when compared with mature IGF-II (15). However, whether posttranslational processing of pro-IGF-II or the balance of mature and big forms are important regulators of placental and fetal growth is not known.…”
mentioning
confidence: 99%